Respostas

A melhor resposta!
2014-04-27T19:29:17-03:00
A)x²-6x+9=0
x² - 3x - 3x + 9 = 0
x(x-3) - 3(x-3) = 0
(x-3)(x-3) = 0
x = 3 (resp)

B)(x+3)²=1
x+3 = 1 ==> x = -2 ou
x+3 = -1 ==> x = -4

C)(x-5)²=1
x-5 = 1 ==> x = 6 ou
x-5 = -1 ==> x = 4

D)5x(x-6)=10
x(x-6) = 2
x² - 6x - 2 = 0
(x - 3)²  - 9  - 2 = 0
(x-3)² = 11
x - 3 = 
√11 ==> x = 3 + √11 ou
x - 3 =  -√11 ==> x = 3 - √11

E(x-3)(x+5)+6=2x+7
x² + 2x - 15 + 6 - 2x - 7 = 0
x² = 16
x = 4 ou x = -4

F)(x+2)²+4x²=4x(x+2)

x² + 4x + 4 + 4x² - 4x² - 8x = 0
x² - 4x + 4 = 0
(x - 2)² = 0 ==> x = 2


1 5 1